A crise do uso da poesia no ensino médio e nos modos avaliativos de acesso à universidade - Prado, Gyannini Jácomo Cândido do (2014)
Understanding how the status of literature is in the first decade of this century is the purpose of this study, from the University access contests. The aim is to clarify the situation of the presence of literature in general and the poem in particular the evidence of English language and literature in the Vestibular the Federal University of Goiás and the National Secondary Education Examination, as Poetry use of sampling in high school. Knowing the literature, as well as the various fronts of human knowledge, the processes suffer front teaching modes. We know, of course, that literature and his studies undergo micro and macro-structural crises and understand these moments becomes necessary, it is by this reflection that may interfere with the day to day teaching of this discipline. Accordingly, the use made of the literature of evidence items for understanding the reality of subjectivity and its objectification is studied.